If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(m + 3) + 7m = 3(m + 10) Reorder the terms: 5(3 + m) + 7m = 3(m + 10) (3 * 5 + m * 5) + 7m = 3(m + 10) (15 + 5m) + 7m = 3(m + 10) Combine like terms: 5m + 7m = 12m 15 + 12m = 3(m + 10) Reorder the terms: 15 + 12m = 3(10 + m) 15 + 12m = (10 * 3 + m * 3) 15 + 12m = (30 + 3m) Solving 15 + 12m = 30 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 15 + 12m + -3m = 30 + 3m + -3m Combine like terms: 12m + -3m = 9m 15 + 9m = 30 + 3m + -3m Combine like terms: 3m + -3m = 0 15 + 9m = 30 + 0 15 + 9m = 30 Add '-15' to each side of the equation. 15 + -15 + 9m = 30 + -15 Combine like terms: 15 + -15 = 0 0 + 9m = 30 + -15 9m = 30 + -15 Combine like terms: 30 + -15 = 15 9m = 15 Divide each side by '9'. m = 1.666666667 Simplifying m = 1.666666667
| 9p+3=7p+4 | | 23x-3=3x+9 | | 9.5=3f-22 | | 16t^2-32t+5=0 | | 2x^2+12xy=-18y^2 | | 96=-6x | | 8(7x-3)=39 | | -30.7/-3 | | 2x^2-12xy=-18y^2 | | -13c+c= | | 1.75x-0.75x=2.5 | | 5-2x+2x=5 | | 12a-6=9+7a | | 2y^3-13y^2+15y=0 | | -30=n-12 | | x^3-6x^2=3x-18 | | 8v=20.48 | | 9x+3x=6 | | 13c+c= | | -2.2=c-(-.80) | | x^3-2x^2+18=4x | | -20.7+-10=-30.7 | | 1=a-9 | | 2.56=2x | | 3y-3x=180 | | 2p+7=11p-11 | | 6x^2-7x=24 | | 2x^2-10xy-3x+15y= | | -9+y=6 | | -240=12m | | (7y^6)(2y^9)= | | y=-3+-6x |